Multiplying the efficiency and impact of biofortification through metabolic engineering - Straeten, Dominique van der; Bhullar, Navreet K.; De Steur, Hans; Gruissem, Wilhelm; MacKenzie, Donald; Pfeiffer, Wolfgang; Qaim, Matin; Slamet-Loedin, Inez; Strobbe, Simon; Tohme, Joe; Trijatmiko, Kurniawan Rudi; Vanderschuren, Hervé; et al. (Springer, 2020)
Ending all forms of hunger by 2030, as set forward in the UN-Sustainable Development Goal 2 (UN-SDG2), is a daunting but essential task, given the limited timeline ahead and the negative global health and socio-economic impact of hunger. Malnutrition or hidden hunger due to micronutrient deficiencies affects about one third of the world population and severely jeopardizes economic development. Staple crop biofortification through gene stacking, using a rational combination of conventional breeding and metabolic engineering strategies, should enable a leap forward within the coming decade. A number of specific actions and policy interventions are proposed to reach this goal.